2017
DOI: 10.3389/fpls.2016.01968
|View full text |Cite
|
Sign up to set email alerts
|

Non-photochemical Quenching Plays a Key Role in Light Acclimation of Rice Plants Differing in Leaf Color

Abstract: Non-photochemical quenching (NPQ) is an important photoprotective mechanism in rice; however, little is known regarding its role in the photosynthetic response of rice plants with differing in leaf color to different irradiances. In this study, two rice genotypes containing different chlorophyll contents, namely Zhefu802 (high chlorophyll) and Chl-8 (low chlorophyll), were subjected to moderate or high levels of light intensity at the 6-leaf stage. Chl-8 possessed a lower chlorophyll content and higher chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 93 publications
1
44
1
Order By: Relevance
“…Lower Fv/Fm and qP under stress conditions (waterlogging and Foph) may be due to the fact that these factors cause leaf photosynthetic pigments degradation, a high ethylene and reactive oxygen species (ROS) production which affect the biochemical function of chloroplasts [24,91,92]. Likewise, NPQ is an important plant photoprotective mechanism to abiotic and biotic stress conditions [95]. In this study, high NPQ values were mainly observed in cape gooseberry plants inoculated with Foph and subjected to waterlogging periods.…”
Section: Chlorophyll Fluorescence Parametersmentioning
confidence: 68%
“…Lower Fv/Fm and qP under stress conditions (waterlogging and Foph) may be due to the fact that these factors cause leaf photosynthetic pigments degradation, a high ethylene and reactive oxygen species (ROS) production which affect the biochemical function of chloroplasts [24,91,92]. Likewise, NPQ is an important plant photoprotective mechanism to abiotic and biotic stress conditions [95]. In this study, high NPQ values were mainly observed in cape gooseberry plants inoculated with Foph and subjected to waterlogging periods.…”
Section: Chlorophyll Fluorescence Parametersmentioning
confidence: 68%
“…This finding was strongly supported by differences in the chloroplast ultrastructure and leaf coloration of wt and ch1 rice, thereby suggesting that the lower accumulation of Chl contents was responsible for the lower Chl b content and higher Chl a/b ratio of the ch1 rice. During photosynthesis, light energy is captured by pigments in the LHC proteins, which then transfer absorbed light energy to PSI and PSII reaction center complexes (Goral et al 2012, Zhao et al 2017. In a previous study of a Chl-deficient A. thaliana mutant, LHC protein was strongly reduced, or even completely absent, thereby impairing the grana stacking of the plant's chloroplast (Kim et al 2009).…”
Section: Chloroplast-related Degs and Photosynthetic Capacitymentioning
confidence: 99%
“…In case of our experiments, NPQ also increased in the CHT-treated tomato leaves at dawn. NPQ could alleviate photodamage by reducing ROS production and could improve photosynthesis at this crucial daytime [56]. These results suggest that CHT perception on the epidermis of intact leaves, which provides the first line of plant defence system, induces significant changes in the photosynthetic activity and in the signalling and metabolism of mesophyll cells in the early light phase thus can contribute to promote defence responses in leaves and plants.…”
Section: Daytime and Light Dependency Of Photosynthetic Activitymentioning
confidence: 81%